2023
DOI: 10.2196/45812
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners’ Experiences With Potentials and Pitfalls of Video Consultations in Norway During the COVID-19 Lockdown: Qualitative Analysis of Free-Text Survey Answers

Abstract: Background The use of video consultations (VCs) in Norwegian general practice rapidly increased during the COVID-19 pandemic. During societal lockdowns, VCs were used for nearly all types of clinical problems, as in-person consultations were kept to a minimum. Objective This study aimed to explore general practitioners’ (GPs’) experiences of potentials and pitfalls associated with the use of VCs during the first pandemic lockdown. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In contrast, almost 60% found it unproblematic to extend a sickness certificate without physical attendance. This is in line with the findings of a recent Norwegian study on GPs’ experiences with video consultation [ 21 , 23 ]. The interviewed GPs confirmed that they would not issue a sickness certification without prior knowledge of the patient and the medical problem and thus found that remote consultations are particularly suitable for the follow-up of chronic and long-term diseases.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, almost 60% found it unproblematic to extend a sickness certificate without physical attendance. This is in line with the findings of a recent Norwegian study on GPs’ experiences with video consultation [ 21 , 23 ]. The interviewed GPs confirmed that they would not issue a sickness certification without prior knowledge of the patient and the medical problem and thus found that remote consultations are particularly suitable for the follow-up of chronic and long-term diseases.…”
Section: Discussionsupporting
confidence: 92%
“…GPs have raised concerns that video consultations might cause clinical uncertainty and lower the threshold for sick leave. 24 In contrast, the results from this survey showed that only 10% of the respondents thought that the GP would have obtained more information through an office appointment. The qualitative opinions indicated that the communication in remote consultations could be poorer due to loss of body language and unspoken signals, misunderstandings, under-communication and over-communication.…”
Section: Discussionmentioning
confidence: 66%
“… 23 24 At the same time, some GPs were concerned that video consultations might cause clinical uncertainty due to loss of valuable communicative information and lower the threshold for sick leave. 24 No research has been conducted on how patients experience receiving a sick leave certificate via remote consultations. The contact with healthcare providers, most often GPs, plays a role in preventing sickness absence or shortening sick leave duration.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has added to the evolving literature about the role of primary care during the COVID-19 pandemic. 15 , 16 , 18 , 22 , 25 By international comparison, Norway had very low and even subnormal mortality rates during the pandemic. 26 This outcome has complex explanations, 26 as outlined in Box 2 and a Norwegian report on the pandemic from 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Two articles about GPs’ reported use of video consultations have been published from the same material. 17 , 22 …”
Section: Methodsmentioning
confidence: 99%